Enhancing reproducibility in neuroimaging with containerized archival - Michael E. Kim; Praitayini Kanakaraj; Yihao Liu; Trent Schwartz; Zhiyuan Li; Nancy R. Newlin; Chenyu Gao; Kurt G. Schilling; Shunxing Bao; Baxter P. Rogers; Bennett A. Landman; Karthik Ramadass (Brain Imaging and Behavior, 2026)
Ensuring reproducibility in scientific research is crucial for validating findings, advancing knowledge, and fostering trust within the scientific community. Containerization of code is a widespread practice to help ensure reproducibility in neuroimaging research. However, there exists no universal method of sharing containers, nor is it feasible to broadly enforce rules due to the diversity of research practices. We posit that container sharing should include 1.) public availability, 2.) self-contained documentation, and 3.) procedures to ensure consistency of the container and its expected outputs. We demonstrate an approach for publicly releasing three separate containers using Zenodo. Our proposed method fulfills the design criteria for container sharing while incurring minimal overhead. As there are several tools available to distribute and maintain containers already, we discuss available alternatives.

Assessing the joint effects of brain aging and gut microbiota on the risks of psychiatric disorders - Huijie Zhang; Li Liu; Shiqiang Cheng; Yumeng Jia; Yan Wen; Xuena Yang; Peilin Meng; Chun’e Li; Chuyu Pan; Yujing Chen; Zhen Zhang; Jingxi Zhang; et al. (Brain Imaging and Behavior, 2022)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)